2023
DOI: 10.3390/cancers15215209
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Ferroptosis to Overcome Drug Resistance in Colorectal Cancer: Promising Therapeutic Approaches

Xiaofei Cheng,
Feng Zhao,
Bingxin Ke
et al.

Abstract: Drug resistance remains a significant challenge in the treatment of colorectal cancer (CRC). In recent years, the emerging field of ferroptosis, a unique form of regulated cell death characterized by iron-dependent lipid peroxidation, has offered new insights and potential therapeutic strategies for overcoming drug resistance in CRC. This review examines the role of ferroptosis in CRC and its impact on drug resistance. It highlights the distinctive features and advantages of ferroptosis compared to other cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 135 publications
0
5
0
Order By: Relevance
“…The field of GI cancer immunotherapy is rapidly evolving, with continuous investigations focusing on deciphering the intricacies of drug resistance and devising innovative approaches to overcome this hurdle. [ 57 ] The future of this field holds promise, but also presents challenges that need to be addressed. One of the potential future directions in this field is the development of personalized immunotherapies.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The field of GI cancer immunotherapy is rapidly evolving, with continuous investigations focusing on deciphering the intricacies of drug resistance and devising innovative approaches to overcome this hurdle. [ 57 ] The future of this field holds promise, but also presents challenges that need to be addressed. One of the potential future directions in this field is the development of personalized immunotherapies.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Additionally, GPX4 prevents ferroptosis, making it a potential target for therapeutic interventions, including cancer treatment (Forcina and Dixon, 2019). Due to frequent m6A and m5c modification of GPX4 in CRC, it is highly overexpressed (Chen B. et al, 2023;, leading to anti-cancer immunity (Chen B. et al, 2023), radiation resistance (Zhang et al, 2023c), and chemoresistance (Wang L. et al, 2023). The increased presence of GPX4 is detected in CRC persister cells resulting from exposure to anti-colorectal cancer drugs like 5-FU and AZ628.…”
Section: System XC − and Gpx4 Inhibitorsmentioning
confidence: 99%
“…Many articles have highlighted the significance of targeting ferroptosis for the treatment of colorectal cancer ( Zhang et al, 2023a ; Liang H. et al, 2023 ; Cheng et al, 2023 ; Liu et al, 2024 ). Therefore, this review aims to present a comprehensive perspective on the impact of natural products on proteins and pathways associated with ferroptosis in CRC ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, several studies have suggested that aspirin is involved in the modulation of ferroptosis in many diseases, including chronic kidney disease and cancer [183][184][185][186]. Most importantly, the modulation of ferroptosis by aspirin has been suggested as a mechanism for the treatment of different untreated cancers, anticancer drug resistance, and metastasis [187][188][189][190][191][192][193][194]. Similarly, iron and other transition metal complexes of aspirin and aspirin-based compounds have been suggested as new anticancer agents [195].…”
Section: Interactions Of Aspirin (Acetylsalicylic Acid) and Its Glucu...mentioning
confidence: 99%
“…A major unexplored area of great importance in pharmacology and medicine is the effects of aspirin and ACM, as well as their iron complexes, on ferroptosis, which is a recently identified type of programmed cell death based on iron-catalysed lipid peroxidation damage of cell membranes [179][180][181][182][183][184]. Ferroptosis has been identified in almost all diseases, including cancer and neurodegeneration [179][180][181][182][183][184][185][186][187][188][189][190]. Several preliminary investigations have already implicated aspirin in the process of ferroptosis via different mechanisms [192][193][194].…”
Section: Future Studies and Limitations On The Role Of Aspirin In Iro...mentioning
confidence: 99%